Analisis Pengaruh Komitmen Organisasi, Pengawasan, dan Insentif Terhadap Kinerja Karyawan - Irsyan, Andrian; Absah, Yenni; Lubis, Arlina Nurbaity (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
The purpose of this study is to find out and analyze how organizational commitment, supervision, and incentives together affect the performance of employees in the Tirta Nauli Regional Water Company Sibolga City. The population in the study was 108 people and the sample was 52 people. Data collected by questionnaire and interview. The analytical method used is multiple regression analysis. The research results obtained where the determination test shows the variable organizational commitment, supervision, and incentives are able to affect the performance variable. Organizational commitment supervision and incentives together have a positive and significant effect on employee performance. Partially organizational commitment positive and significant effect on employee performance. Partially supervision positive and significant effect on employee performance. Partially incentives positive and significant effects on employee performance. Of the third independent variable covering organizational commitment, supervision, and incentives is known that partially incentives variable have the most dominant influence on employee performance.